Review and Prospect of Research on Physical Education Teaching Evaluation in Chinese Universities - LI, Xuwu; YU, Zhong (Journal of Educational Research and Policies, 2025)
The research on the evaluation of physical education teaching in Chinese higher education institutions has gone through a shift from the basic theory of teaching evaluation, to teaching evaluation methods and means, and then to the research on teaching evaluation results. Its development trajectory has reference and reflective significance for the subsequent research on the evaluation of physical education teaching in higher education institutions. This article adopts methods such as literature review and logical analysis to systematically sort out the preliminary research on the evaluation of physical education teaching in universities. It is found that the research on the basic theory of teaching evaluation mainly adheres to a theoretical orientation, covering various aspects such as the basic connotation, essence, characteristics, classification, principles, guiding ideology, and methods of teaching evaluation; The research on evaluation methods and means mainly involves exploring which evaluation methods can be used more scientifically and effectively to evaluate physical education teaching; Research on the evaluation of teaching effectiveness mainly explores whether the effectiveness of physical education teaching should be guided by value or quality. Looking ahead to the future, research on physical education teaching evaluation in Chinese higher education institutions should start from national tasks and social needs, expand the existing research boundaries of physical education teaching evaluation, and pay attention to the entry of research perspectives. Efforts should be made to broaden the research perspectives of physical education teaching evaluation as much as possible, in order to better guide the development of physical education teaching evaluation research in a positive direction.